FACTORS RELATING TO WORK FATIGUE IN LOCOMOTIVE DIPO WORKERS PT. KERETA API INDONESIA (PERSERO) - Sari Narulita Purwati Ningsih (Universitas Darussalam Gontor, 2018)
Work fatigue is one of the health and safety issues that can be a factor of work accident. Work fatigue can be influenced by internal and external factors. Work fatigue can have an impact on decreasing work productivity and decreasing work concentration. The purpose of this study was to determine the factors associated with work fatigue workers of Dipo Lokomotif Sidotopo PT. Kereta Api Indonesia Operation Area 8 Surabaya. The design of this research was using cross sectional approach. The population of this research was 84 workers and sample of 45 workers. The dependent variable in this study were work fatigue, and the independent variables were internal factors (age, length of working, nutritional status) and external factors (workload, work shift, noise intensity). The collecting data technique that used in this research was using a 30-item questionnaire of IFRC general fatigue symptoms (International Fatigue Research Committee of Japanese Association of Industrial Health) and quistionaire for internal and external factors. The results showed that was most felt by workers fatigue was mild (51.1%). There was a relationship between work period, shift work and noise intensity. There is no significant relationship between age, workload and nutritional status. To reduce work fatigue, PT. Kereta Api Indonesia Operation Area 8 Surabaya have to conduct routine physical exercise (gymnastics) to the worker, and educate workers about the importance of minimizing the risk of fatigue.Keywords : Fatigue, Intenal Factors, Eksternal Factors